Post a New Question

algebra

posted by on .

Simplify the following expression, and rewrite it in an equivalent form with positive exponents. 10x^3y^3
--------
40x^-3y^-4

  • algebra - ,

    10x^3y^3
    --------
    40x^-3y^-4

    Use the law of negative exponents:
    1/a^x = a^(-x)

    10x^3y^3
    --------
    40x^-3y^-4
    =(10/40) x^3y^3 * x^-(-3)y^-(-4)
    =(1/4) x^3*x^3 * y^3*y^4
    =(1/4)x^6 y^7

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question